Emotion regulation and job satisfaction levels of employees working in family and non-family firms - Duarte Pimentel; Ana Pereira (Administrative Sciences, 2022)
The purpose of this paper is to explore the differences between employees working in family and non-family firms regarding their emotion regulation and job satisfaction levels. Moreover, focusing on family firms, we assess the relationship between the employees' emotion regulation and job satisfaction levels. The empirical evidence is provided by a sample of 178 Portuguese employees, 80 employees of family firms, and 98 non-family firms' employees, who responded to a questionnaire that included emotion regulation and job satisfaction measures. All respondents work in small- and medium-sized private companies. Although the results do not confirm the first hypothesis, suggesting that employees working on family firms show higher levels of emotion regulation than those of non-family companies, the idea that employees of family companies show higher levels of job satisfaction than employees of non-family companies is confirmed (i.e., Hypothesis 2). Moreover, the results also support the third hypothesis, confirming that emotion regulation levels have a significant and positive relationship with the job satisfaction levels of employees working in family firms. This paper makes several contributions to the research literature by addressing two organizational aspects still under-addressed in the comparison between family and non-family firms, while pursuing to offer insights on the relationship between the emotion regulation and job satisfaction levels of employees working in family firms.
Keywords: 350; family business; emotion regulation; job satisfaction